KINERJA KEUANGAN PERUSAHAAN TERHADAP PENETAPAN TINGKAT SEWA OBLIGASI SYARIAH IJARAH DI INDONESIA - Yuliana, Indah (IQTISHODUNA, 2012)
During the period of January to July 2008, the establishment of corporate sukuk has reached 12,5 % from a total is suance of corporate bonds or at Rp. 1,62 trillion. This amount has exceeded the total sukuk issuance during 2007 which amounted to Rp. 1.03 trillion. In fact skim ijarah (rents) in value is prospective for the I’ssuer intends to issue Islamic bonds. Although ijarah Islamic bond appeared after 2 years of Islamic bonds mudarobah.. Performance and risks faced by companies in influenced by internal and external factors. Financial report is one tool to report the position of the company at a particular point in time during one period. The value of the financial statements lies in the report can be used to evaluated company’s current performance and predict future from the stand point of management, financial statement analysis will be useful to help anticipate the future and as starting point for planning steps that will improve company performance in the future. The research objective was to see the influence of the company’s financial performance against the Islamic bond lease. Research sites are in PT Kustodian sentral efek Indonesian. This research is a type of quantitative research.